Urban traffic-derived nanoparticulate matter reduces neurite outgrowth via TNFα in vitro. Issue 1 (December 2016) - Cheng, Hank; Davis, David; Hasheminassab, Sina; Sioutas, Constantinos; Morgan, Todd; Finch, Caleb
Abstract Background The basis for air pollution-associated neurodegenerative changes in humans is being studied in rodent models. We and others find that the ultrafine particulate matter (PM) derived from vehicular exhaust can induce synaptic dysfunction and inflammatory responses in vivo and in vitro. In particular, a nano-sized subfraction of particulate matter (nPM, PM0.2) from a local urban traffic corridor can induce glial TNFα production in mixed glia (astrocytes and microglia) derived from neonatal rat cerebral cortex. Methods Here, we examine the role of TNFα in neurite dysfunctions induced by nPM in aqueous suspensions at 12 μg/ml. First, we show that the proximal brain gateway to nPM, the olfactory neuroepithelium (OE), rapidly responds to nPM ex vivo, with induction of TNFα, activation of macrophages, and dendritic shrinkage. Cell interactions were further analyzed with mixed glia and neurons from neonatal rat cerebral cortex. Results Microglia contributed more than astrocytes to TNFα induction by nPM. We then showed that the threefold higher TNFα in conditioned media (nPM-CM) from mixed glia was responsible for the inhibition of neurite outgrowth by small interfering RNA (siRNA) TNFα knockdown and by TNFα immunoneutralization. Despite lack of TNFR1 induction by nPM in the OE, experimental blocking of TNFR1 by TNFα receptor blockers restored total neurite length. Conclusions These findings implicate microglia-derived TNFα as a mediator of nPM in air pollution-associated neurodegenerative changes which alter synaptic functions and neuronal growth.